2022
DOI: 10.1186/s12864-022-08372-4
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative multiplexed proteomics analysis reveals reshaping of the lysine 2-hydroxyisobutyrylome in Fusarium graminearum by tebuconazole

Abstract: Backgrounds Lysine 2-hydroxyisobutyrylation (Khib) is a newly discovered posttranslational modification (PTM) and has been identified in several prokaryotic and eukaryotic organisms. Fusarium graminearum, a major pathogen of Fusarium head blight (FHB) in cereal crops, can cause considerable yield loss and produce various mycotoxins that threaten human health. The application of chemical fungicides such as tebuconazole (TEC) remains the major method to control this pathogen. However, the distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 100 publications
0
9
0
Order By: Relevance
“…Subsequently, the profiling of 2hydroxyisobutyrylome in different species was reported, which mainly lied on the efficient affinity enrichment at proteome-wide with confirmed anti-2-hydroxyisobutyryllysine antibody conjugated agarose beads and LC-MS/MS analysis. Until now, thousands of Khib proteins have been identified in animal [12,18,20,21], fungi [13,[22][23][24][25][26][27][28][29],…”
Section: Global Analysis Of Lysine 2-hydroxyisobutyrylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, the profiling of 2hydroxyisobutyrylome in different species was reported, which mainly lied on the efficient affinity enrichment at proteome-wide with confirmed anti-2-hydroxyisobutyryllysine antibody conjugated agarose beads and LC-MS/MS analysis. Until now, thousands of Khib proteins have been identified in animal [12,18,20,21], fungi [13,[22][23][24][25][26][27][28][29],…”
Section: Global Analysis Of Lysine 2-hydroxyisobutyrylationmentioning
confidence: 99%
“…Photosynthesis occurs in chloroplasts and stores energy as chemical bonds in sugars. The Calvin cycle (also known as the Calvin-Benson cycle, carbon fixation in photosynthetic organisms) refers to the light-independent steps of photosynthesis that convert carbon dioxide (CO 2 ) into carbohydrates and other organic compounds [28,29]. PTMs control multiple proteins and enzymes that are essential to photosynthesis at various stages.…”
Section: Comparison Of 2-hydroxyisobutyrylome In Different Organismsmentioning
confidence: 99%
“…In agricultural practice, there are multiple threats to wheat production, especially severe plant diseases, such as FHB (Fusarium head blight) disease, which causes significant reductions in grain quality and quantity. The FHB epidemic has been reported to lead to a 10–70% wheat production loss. , Besides quality losses, disease progress is accompanied by the production of trichothecene mycotoxins, which pose a severe threat to the health of human beings and livestock. , Therefore, various management strategies have been developed to control FHB, for instance agricultural practices, breeding, chemical control, etc. Among them, the use of chemical fungicides remains the most effective control strategy. , However, the dependency on chemical fungicides in FHB management practices raises extensive concerns about environmental pollution, human and animal health, as well as resistance development. ,, As a result, it is both promising and challenging to develop and utilize biofungicides, the alternative of chemical fungicides.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 However, the dependency on chemical fungicides in FHB management practices raises extensive concerns about environmental pollution, human and animal health, as well as resistance development. 7,13,14 As a result, it is both promising and challenging to develop and utilize biofungicides, the alternative of chemical fungicides.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that this modification also occurs in nonhistone proteins in various compartments of cells. To date, K hib modification has been identified in human or animal [9][10][11][12][13], fungus (Aspergillus flavus [14], Fusarium graminearum [15], Candida albicans [16], bacteria (Proteus mirabilis [17] and Toxoplasma gondii [18]) and plants. All these studies indicate that K hib modification is not only widely present in various organisms, but also involved in a wide variety of physiological functions.…”
Section: Introductionmentioning
confidence: 99%